Analisis Pemikiran Abuddin Nata: Mengatasi Kelemahan Pendidikan Islam di Indonesia Sebagai Upaya Peningkatan Mutu Pembelajaran PAI - Laila Rahmi Hasanah; Asiana; M. Albab Mananna; Mardiah Astuti; Hartatiana (Sekolah Tinggi Ilmu Tarbiyah Al-Bukhary Labuhanbatu, 2026)
The phenomenon of Islamic education development in Indonesia presents challenges in curriculum quality, teaching methods, and educator professionalism. This study aims to analyze Abuddin Nata’s ideas to address these weaknesses for improving the quality of Islamic Religious Education (PAI). This juridical-normative research employs a descriptive qualitative method. The population includes Abuddin Nata’s works and relevant literature from 2021-2025, with purposive sampling. Data were collected through documentation and analyzed via triangulation. Findings reveal weaknesses in teacher professionalism, conventional teaching methods, and infrastructure disparities. Quantum teaching emerges as an innovative method that enhances student motivation and creativity. The study concludes that Nata’s thought offers an integrated solution involving management improvements, integration of religious and general knowledge, and strengthening educator competencies to improve the quality of Islamic Religious Education in Indonesia.